2019
DOI: 10.3847/1538-3881/ab21e0
|View full text |Cite
|
Sign up to set email alerts
|

The Detectability and Characterization of the TRAPPIST-1 Exoplanet Atmospheres with JWST

Abstract: The James Webb Space Telescope (JWST) will offer the first opportunity to characterize terrestrial exoplanets with sufficient precision to identify high mean molecular weight atmospheres, and TRAPPIST-1's seven known transiting Earth-sized planets are particularly favorable targets. To assist community preparations for JWST observations, we use simulations of plausible post-ocean-loss and habitable environments for the TRAPPIST-1 exoplanets, and test simulations of all bright object time series spectroscopy mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
279
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 225 publications
(306 citation statements)
references
References 100 publications
9
279
0
Order By: Relevance
“…Thus, a Venus-like atmosphere as well water vapor might be a plausible solution to the atmospheric compositions of the TRAPPIST-1 planets, which is favored by their flat and featureless transmission spectra. If the TRAPPIST-1 planets possess terrestrial-like atmospheres containing CO 2 , CO 2 absorption will be detectable in transmission spectra acquired in less than 10 transits with James Webb Space Telescope/NIRSpec Prism, although the detection of O 2 and O 3 will be still be elusive (Lustig-Yaeger et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a Venus-like atmosphere as well water vapor might be a plausible solution to the atmospheric compositions of the TRAPPIST-1 planets, which is favored by their flat and featureless transmission spectra. If the TRAPPIST-1 planets possess terrestrial-like atmospheres containing CO 2 , CO 2 absorption will be detectable in transmission spectra acquired in less than 10 transits with James Webb Space Telescope/NIRSpec Prism, although the detection of O 2 and O 3 will be still be elusive (Lustig-Yaeger et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Because TRAPPIST-1 is not continuously visible, Lustig-Yaeger et al (2019) find that JWST will have 123 opportunities in its nominal 5 year lifetime to observe the transit of TRAPPIST-1d, which has an orbital period of 4.05 days. Assuming the same visibility as TRAPPIST-1, the number of observable transits would decrease to 31 for a planet with an orbital period of 16 days.…”
Section: Detectability Of Molecular Featuresmentioning
confidence: 99%
“…Recent climate modeling has begun to explore how clouds affect the detection of transmission spectral features with JWST. Using the one-dimensional climate and photochemical models of Lincowski et al (2018), Lustig-Yaeger et al (2019) found that clouds inhibit the detection of water features on TRAPPIST-1e. However, three-dimensional simulations are necessary to accurately simulate cloud and water vapor mixing ratios.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, results suggest that a few bars of surface CO 2 are needed to maintain ice-free surfaces on TRAPPIST-1f and g. Grimm et al (2018) has found that while TRAPPIST-1e may have a large rocky interior, TRAPPIST-1f and -1g are likely to be volatile rich. Note that 1-D climate model simulations have also been used for TRAPPIST-1 planets (Morley et al 2017;Lincowski et al 2018;Lustig-Yaeger et al 2019) with the limitations of this approach described earlier. For instance, in their simulated transmission spectra Morley et al (2017), considers clear sky atmospheres, while it is not realistic when H 2 O or CO 2 are in the atmosphere and could eventually form clouds, or CH 4 and H 2 SO 4 which could form organic and sulfuric hazes.…”
Section: Introductionmentioning
confidence: 99%